The greatest good for the greatest number of people: an Islamic philosophical analysis - Md Abdul Jalil,; Naail Mohammed Kamil,; Muhammad Khalilur Rahman, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2014)
The western ethical philosophy provides that if any decision brings the greatest good for the greatest number of people, then the decision is acceptable although a small number of people might be affected by the decision. This is also known as democratic rule of making decision based on majority opinions. There are similar principles in Islam known as ‘al-maslahah al-mursalah’ which means ‘for public interest’. It means that if any decision is taken by a business leader or by an authority for the interest of employees or the public then that decision is acceptable in Islamic jurisprudence. Islam accepts a decision if it is beneficial for the society. There is another principle in Islam which is known as ‘Istihsan’ which means ‘judicial preference’. Muslim scholars use this concept to prefer one decision over another on public interest ground. However, it is noteworthy that as mankind, we are the vicegrants (Khalifa) of Allah (Subhanahu Wa Ta’alaa) on earth as well as representatives of the general masses of the society. So, whatever decision which is formulated, it should be for the benefit of people and at the same time for the satisfaction and contentment of Allah (Subhanahu Wa Ta’alaa). The objective of this paper is to critically analyze the possibility of harmonizing the western philosophy ‘the greatest good for the greatest number of people’ with the Islamic jurisprudential principles ‘al-maslahah al-mursalah’ and ‘al-Istihsan’. Qualitative research approach was employed in this study to critically analyze the above mentioned jurisprudential principles.